A Systematic Literature Review on ICTD Research by IS Community - Luthfi Ramadani (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2017)
Despite a huge number of Information and Communications Technology for Development (ICTD) research so far, little is known about the landscape of published articles in Information Systems (IS) literature. This paper systematically reviews extant ICTD research published in the IS field from 1980-2016. The author systematically analyzed 192 articles published in A* and A-rank IS journals and explored which theoretical lenses, contexts, units of analysis, types of technology, and research methods dominate extant research in the field. As such, this present work provides a unique snapshot of the current research landscape that can help future ICTD field progress.